Cahiers de prison : cahiers 1, 2, 3, 4 et 5 - Gramsci, Antonio; Aymard, Monique; Bouillot, Françoise; Paris, Robert ([Paris] : Gallimard, 1996)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie